E-048 Flow characteristics of three toroidal aneurysms. (4th July 2012) - Hui, F; Piccinelli, M; Passerini, T; Spiotta, A; Moskowitz, S; Tong, F; Veneziani, A
Abstract : Introduction: Donut-shaped, or Toroidal aneurysms are a rare angiographic morphology wherein an intraluminal thrombus forms at the center of the aneurysm sac, creating a "hole" in the flow of blood. Formation of these "cross-bars" of clot is presumably related to flow characteristics related to the shape of the aneurysm sans-thrombus. Methods: In these computational flow dynamics (CFD) investigations, assessment of the native flow characteristics was made, as well as CFD for the lesion with the axial thrombus mathematically removed from the model to assess probable flow characteristics. Findings and conclusion: CFD findings show flow characteristics are displayed. And discussion of further directions of analysis will be given. Competing interests: None.